The effect of a new communication template on anticipated willingness to initiate or resume allergen immunotherapy: an internet-based patient survey - Calderón, Moisés A.; Pfaar, Oliver (Allergy, asthma and clinical immunology, 2015)
Background: A patient’s knowledge of his/her allergic condition and treatment is a key factor in adherence and effectiveness. Methods: To assess patients’ understanding of allergy and acceptance of allergen immunotherapy on the basis of (i) information given by their physician at the time of prescription and (ii) a new communication template viewed some months later, we performed an Internet-based survey of patient panels in France, Germany, Spain, the USA and Russia. The survey participants were either recent “early abandoners” (having discontinued allergen immunotherapy before the end of the prescribed course) or “non-starters” (having decided not to initiate a course of allergen immunotherapy recommended by their physician). All participants completed an on-line questionnaire immediately before and immediately after viewing the new communication template. The study’s main objectives were to validate the new communication template and to assess its impact on anticipated willingness to initiate or resume allergen immunotherapy. Results: We surveyed a total of 261 patients (France: 57; Germany: 51; Spain: 52; USA: 51; Russia: 50), comprising 127 “early abandoners” and 134 “non-starters”. The mean time since symptom onset and selection for the study was 14.5 years. Subcutaneous allergen immunotherapy had been prescribed in 60 % of cases. Twenty-eight percent of the participants did not know for which allergy they were being treated. Early abandoners reported a perception of low effectiveness (39 %) and complained about expense (39 %) and practical constraints (32 %). Twenty-two percent of the non-starters feared side effects. The communication template was considered to be clear (by 92 % of the patients), convincing (by 75 %) and reassuring (by 89 %); 80 % of the participants felt better informed afterwards, and 67 % stated that viewing the communication template would have made them more likely to continue or initiate allergen immunotherapy (overall willingness score: 5.65 out of 10 before viewing and 7.1 out of 10 afterwards). Conclusions: After viewing a new communication template on allergy and allergen immunotherapy, patients participating in the survey felt better informed and more likely to initiate or complete this therapy. It now remains to investigate the communication template’s effect on actual acceptance of and adherence to allergen immunotherapy.